Determination of Fatty Acid Composition of Two Carp Species by GC-MS - Horj, E.; Iordache, A.; Toma, A.; Cozar, O.; Culea, M. (Asian Journal of Chemistry, 2011)
A gas chromatography-mass spectrometric (GC/MS) technique was used to evaluate effects in quantitative fatty acids in fish plasma after Se addition in food, 0.03 mg/kg, in comparison with control. Selenium is a potent antioxidant protecting the body from damage due to oxidation by free radicals. Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are the major fatty acids found in fish. These fatty acids are produced by unicellular algae and phytoplankton which are consumed and then accumulate in fish. The aim of this work was to establish the extraction procedure and quantitative method of the fatty acids from fish plasma. The fatty acids were derivatized to obtain methyl esters. The identification of fatty acids was obtained by comparison of fatty acids methyl esters mass spectra with the mass spectra of fatty acids methyl esters kits and of NIST library. Concentrations of majority of unsaturated fatty acids increased with Se supplementation.